EFEKTIVITAS PIJAT PADA TITIK AKUPUNTUR GUANYUAN (RN4) DAN QIHAI (RN6) TERHADAP DISMENORE PADA SISWI SMKN 1 SURABAYA - Afiyah, Raden Khairiyatul; Umamah, Farida (JURNAL NERS LENTERA, 2019)
Menstrual pain (dysmenorrhea) in students may interference daily activities. Handling menstrual pain (dysmenorrhea) can be done one of them with non-pharmalogical treatment of massage in Guanyuan (RN 4) and Qihai (RN 6) acupunture points. The purpose of this study to find out the effectiveness of massage in Guanyuan (RN 4) and Qihai (RN 6) acupunture points on dismenore in students of SMKN 1 Surabaya. Study design is Pre Experimental approaches One-group pre-post test design, the population 200 students of Class of XI with the number of respondents 100 who has menstrual pain (dysmenorrhea) and willing to become respondents. Using cluster sampling technique. The independent variables is massage in Guanyuan (RN 4) and Qihai (RN 6) acupunture points and the dependent variable is menstrual pain (dysmenorrhea). Instrument this study uses questionnaire NRS (Numerical Rating Scale), analysis of data use the Wilcoxon signed rank test with ? < 0,05. Study results showed from 100 respondent, most of them The results obtained an average value of the level of menstrual pain (dysmenorrhea) prior to massage at the acupuncture points guanyuan (RN 4) and qihai (RN 6) which is 5.04. After doing massage at the acupuncture points guanyuan (RN 4) and qihai (RN 6) the average value of menstrual pain (dysmenorrhea) is 2.07. Wilcoxon signed rank test got P=0,000 < ? = 0,05 so, H0 is rejected, means massage in Guanyuan (RN 4) and Qihai (RN 6) acupunture points is effective for decrasing menstrual pain (dysmenorrhea) on student of SMKN 1 Surabaya. Massage in Guanyuan (RN 4) and Qihai (RN 6) acupunture points effective in decreasing menstrual pain (dysmenorrhea). Expected nurses can participate in providing health education to perform massage in Guanyuan (RN 4) and Qihai (RN 6) acupunture points as a non-pharmalogical therapy in reducing menstrual pain (dysmenorrhea). Keywords: Guanyuan (RN 4) and Qihai (RN 6) acupunture points, Menstrual pain